Mutagenesis Analysis of ABCB4 Gene Promoter of Danio rerio - YEAW, ZI XUAN; LIM , LEONARD WHYE KIT; CHUNG, HUNG HUI (Trends in Undergraduate Research, 2020)
Zebrafish abcb4 gene (ortholog to human ABCB1 gene) serves primarily in multidrug resistance (MDR) mechanism by effluxing chemotherapeutic agents, chemicals, xenobiotics, and numerous anti-cancer drugs out of the cells. This study aims to identify the specific transcription factor binding sites (TFBS) within the promoter region of zebrafish abcb4 gene and determine the functional roles of these factors in abcb4 gene expression regulation via mutagenesis analysis. First, primers were designed to target and amplify the promoter region of zebrafish abcb4 gene through gradient PCR. The zebrafish abcb4 gene promoter was then cloned into pGL3.0 vector and sent for sequencing. The sequencing results revealed high similarity to zebrafish DNA sequence from clone DKEY-24I24 in linkage group 16, indicating a successful cloning of targeted gene. Thereafter, consensus sequence of zebrafish abcb4 gene promoter was generated with the length of 1,392 bp which was close to its expected size during primer design (1,500 bp). Using MATCH tool, 155 TFBSs were found within zebrafish abcb4 gene promoter region. Activator protein 1 (AP-1) TFBS at 1,255 bp was chosen to be mutated through site-directed mutagenesis. Mutagenic primers (forward primer: 5’ GGG CAA GGC AGT ATA AAC GTG 3’ and reverse primer: 5’ TTA TGT TTC TAG GGA TTA CGT CAC 3’) were designed to substitute AGT with GGG to remove the AP-1 TFBS. By mutating the zebrafish abcb4 gene promoter, the MDR phenomenon driven by zebrafish abcb4 gene can be elucidated and this might provide clues to the development of tumor and malignancy in human. The results from this study may enrich the knowledge in chemotherapy and cancer treatments.